A high-porosity filling material with rapid and efficient cementation of gangue and preparation method thereof
By adopting the preparation method of frame-type bearing materials in coal mine filling mining, the problem of filling operations interfering with production and insufficient gangue demand is solved, and rapid and efficient cementing of gangue and high porosity, low density and high strength filling materials are achieved, simplifying the The preparation process reduces costs and improves the efficiency and safety of filling operations.
Patent Information
- Application Number
- CN202311170738.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-12
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2043-09-12
AI Technical Summary
In coal mine filling and mining, the existing technology faces the problems of filling operations interfering with normal production, insufficient demand for gangue and high equipment costs, especially in complex geological conditions, it is difficult to achieve rapid and efficient cementing of gangue and high porosity, low density and high strength filling. Material.
Using the preparation method of frame-type bearing materials, the uniaxial and uniaxial can be prepared by laying coal gangue layer by layer in the mold and spraying fast-geling materials, combining static pressure infusion and particle size grading. High-pore filling materials with compressive strength not less than 0.14MPa simplifies the compaction and solidification process and reduces equipment costs.
It realizes rapid and efficient cementing of gangue, significantly shortens the preparation time of filling materials, reduces the impact on working face production, saves the amount of gangue and equipment costs, and improves the safety and efficiency of filling operations.
Smart Images

Figure CN117263581B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of coal mine filling mining, and in particular to a high-porosity filling material with rapid and efficient cementation of gangue and a preparation method thereof. Background Art
[0002] With the continuous increase in demand for coal resources, the focus of coal mining has been continuously shifted to the west and deep in the strata, and higher requirements have been put forward for filling mining technology under complex geological conditions. Filling mining technology can be divided into three categories. The first is the comprehensive mechanized solid / paste filling technology, which refers to the addition of a solid / paste filling system on the basis of the comprehensive mechanized coal mining system to realize parallel operations of coal mining and filling; the second is the longwall cementing filling technology, which refers to the use of the longwall coal mining production system, using an integrated digging and anchoring machine to break coal, and cementing filling materials to fill the connecting tunnels with filling mining technology; the third is the subsequent space gangue grouting filling technology, which realizes the goal of fully separating and large-scale processing of gangue by making gangue into slurry and injecting it into all the pore spaces formed by the overburden after mining. The above three types of filling mining technologies have achieved good development under different mine geological conditions, but they are also facing three major technical bottlenecks:
[0003] 1. The filling operation interferes with normal production, affects the coal output, and thus affects the coal production efficiency. Taking the comprehensive mechanized solid / paste filling technology as an example, the compaction of solid filling materials and the solidification of paste filling materials both affect the normal working process of the hydraulic support such as the shifting of the frame;
[0004] 2. In order to achieve better rock formation control, the demand for filling materials is about 1.3 times the amount of coal mined. Especially for mines with a capacity of tens of millions of tons, the amount of gangue required for large-scale filling mining is seriously insufficient;
[0005] 3. The filling equipment is expensive and the engineering cost is high. The implementation of the filling operation requires the purchase of additional filling supporting equipment, the construction of ground / underground grouting filling stations, etc., which requires huge investment. Summary of the invention
[0006] Technical problem: Provide a frame-type load-bearing filling material and a preparation method thereof to simultaneously achieve rapid and efficient cementation of gangue with high porosity, low density and high strength.
[0007] Technical solution:
[0008] On the one hand, a method for preparing a high-porosity filling material with rapid and efficient cementation of gangue is provided. The method comprises the following steps:
[0009] (1) According to the target porosity of the high-porosity filling material, a layer of coal gangue with a certain particle size distribution is laid on the bottom of the mold, and a fast-bonding material is sprayed into the laid coal gangue layer through a pressurized nozzle so that the fast-bonding material is evenly distributed on the surface of the coal gangue layer;
[0010] (2) laying a layer of coal gangue on the coal gangue layer after spraying the rapid adhesive bonding material, and repeating the above steps to lay coal gangue layer by layer and spray the rapid adhesive bonding material layer by layer until the coal gangue layer reaches the top of the mold, and then covering the upper cover of the mold;
[0011] (3) statically pouring a quick-adhesive cementing material into the mold through the grouting hole on the upper cover until the quick-adhesive cementing material appears at the bottom of the mold and then the pouring is stopped;
[0012] (4) After standing for 0.5 h, a high-porosity filling material is obtained;
[0013] (5) testing the porosity and uniaxial compressive strength of the high-porosity filling material;
[0014] (6) by changing the particle size distribution of the coal gangue in step (1) to change the target porosity of the high-porosity filling material, repeating steps (2) to (5), and establishing a prediction model between the porosity and uniaxial compressive strength of the high-porosity filling material;
[0015] (7) According to step (6), the particle size distribution of coal gangue corresponding to the high-porosity filling material having a porosity of not less than 20% and a uniaxial compressive strength of not less than 0.14 MPa is screened out;
[0016] The fast-adhesive cementing material has a slump of 150 to 200 mm, an initial setting time of less than 10 minutes, and a final setting time of less than 4 hours.
[0017] In some embodiments, the rapid cementing material includes the following components in parts by mass: 140-160 parts of fly ash, 80-120 parts of slag powder, 8-15 parts of cement, 0.8-1.2 parts of cement early strength activator, 2-4 parts of accelerator and 50-70 parts of water.
[0018] In some embodiments, the rapid cementing material includes the following components in parts by mass: 150 parts of fly ash, 100 parts of slag powder, 10 parts of cement, 1 part of cement early strength activator, 3 parts of accelerating agent and 66 parts of water.
[0019] In some embodiments, the high-porosity filling material having a porosity of not less than 20% and a uniaxial compressive strength of not less than 0.2 MPa corresponds to a coal gangue particle size distribution of 0 to 20 mm.
[0020] In some embodiments, the high-porosity filling material having a porosity of not less than 30% and a uniaxial compressive strength of not less than 0.19 MPa corresponds to a coal gangue particle size distribution of 0 to 10 mm.
[0021] In some embodiments, the high-porosity filling material having a porosity of not less than 40% and a uniaxial compressive strength of not less than 0.14 MPa corresponds to a coal gangue particle size distribution of 0 to 5 mm.
[0022] In some embodiments, the mold is transparent.
[0023] In some embodiments, the mold is a hollow cylinder with an inner diameter of 50 mm and a height of 100 mm; a plurality of slurry discharge holes are provided at the bottom of the mold.
[0024] In some embodiments, the diameter of the grouting holes and the grouting holes is 5 mm.
[0025] In some embodiments, the number of the slurry discharge holes is 9, and the slurry discharge holes are evenly distributed on the bottom of the mold.
[0026] On the other hand, a high-porosity filling material with fast and efficient coal gangue bonding obtained by the above-mentioned preparation method is provided. The fast bonding bonding material is attached to the surface of the coal gangue in the form of flocs, and the key contact points between the particles of the coal gangue are bonded by the fast bonding bonding material, and the coal gangue and the fast bonding bonding material are connected layer by layer to form a high-porosity filling material with a porosity of not less than 20% and a uniaxial compressive strength of not less than 0.14MPa.
[0027] Beneficial effects:
[0028] 1. The present invention provides a frame-type load-bearing filling material - a high-porosity filling material with rapid and efficient cementation of gangue. The rapid bonding cementing material allows the gangue to be rapidly bonded at key points, and can simultaneously achieve rapid and efficient cementation of gangue with high porosity (not less than 20%), low density and high strength (uniaxial compressive strength not less than 0.2MPa), which is conducive to the safe and efficient mining of the filling working face.
[0029] 2. The present invention adopts a fast-bonding cementing material with a slump of 150 to 200 mm, an initial setting time of less than 10 minutes, and a final setting time of less than 4 hours. The fast-bonding cementing material has the characteristics of high viscosity, no flow, and fast hardening. It can quickly and efficiently bond the coal gangue, eliminating the compaction and solidification waiting time, significantly shortening the preparation time of the filling material, and greatly reducing the adverse effects on the normal production of the working face.
[0030] 3. The preparation method of the present invention effectively controls the movement of overburden rocks and uses high-porosity filling materials that are quickly and efficiently cemented by low-density and high-porosity gangue, which can effectively reduce the amount of gangue required for filling operations and save costs.
[0031] 4. The present invention adopts a pressurized nozzle to adjust the spraying state of the fast-bonding cementing material and comprehensively spray the surface of the coal gangue in the mold.
[0032] 5. Based on the preparation method of the present invention, the mechanical strength requirements of the high-porosity filling material are determined in combination with the geological conditions of the coal seam, thereby determining the mechanical porosity of the high-porosity filling material.
[0033] 6. Based on the preparation method of the present invention, the existing hydraulic supports in the mine can be modified for filling, thereby effectively reducing equipment costs.
[0034] 7. The high-porosity filling material obtained by the invention with rapid and efficient cementation of gangue has high porosity and huge available space, which provides possibilities for the development of resources in multiple fields such as hydrogen storage, heat storage, and carbon fixation.
[0035] 8. The high-porosity filling material with rapid and efficient cementation of gangue prepared by the present invention has low strength loss (the lowest uniaxial compressive strength loss rate is 8.4%) compared with dense filling bodies. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1 A schematic diagram of the structure of a high-porosity filling material with rapid and efficient cementation of gangue in some embodiments;
[0037] Figure 2 A three-dimensional structural diagram of a mold for preparing a high-porosity filling material for rapid and efficient cementation of gangue in some embodiments;
[0038] Figure 3 for Figure 2 A top view of a mold;
[0039] Figure 4 for Figure 2 Bottom view of the mold. DETAILED DESCRIPTION
[0040] On the one hand, a method for preparing a high-porosity filling material with rapid and efficient cementation of gangue is provided. The method comprises the following steps:
[0041] (1) According to the target porosity of the high-porosity filling material, in the mold 4 (such as Figures 2 to 4 A layer of coal gangue with a certain particle size distribution is laid on the bottom of the coal gangue layer (as shown), and a quick-adhesive bonding material is sprayed into the laid coal gangue layer through a pressurized nozzle so that the quick-adhesive bonding material is evenly distributed on the surface of the coal gangue layer;
[0042] (2) Continue to lay a layer of coal gangue on the coal gangue layer after spraying the rapid adhesive bonding material, and repeat the above steps to lay coal gangue layer by layer and spray the rapid adhesive bonding material layer by layer until the coal gangue layer reaches the top of the mold 4, and then cover the upper cover of the mold 4;
[0043] (3) statically pouring the quick-adhesive cementing material into the mold 4 through the grouting hole 5 on the upper cover until the quick-adhesive cementing material appears at the bottom of the mold 4 and then stopping the pouring;
[0044] (4) After standing for 0.5 h, a high-porosity filling material is obtained;
[0045] (5) testing the porosity and uniaxial compressive strength of the high-porosity filling material;
[0046] (6) by changing the particle size distribution of the coal gangue in step (1) to change the target porosity of the high-porosity filling material, repeating steps (2) to (5), and establishing a prediction model between the porosity and uniaxial compressive strength of the high-porosity filling material;
[0047] (7) According to step (6), the particle size distribution of coal gangue corresponding to the high-porosity filling material having a porosity of not less than 20% and a uniaxial compressive strength of not less than 0.14 MPa is screened out;
[0048] The fast-adhesive cementing material has a slump of 150 to 200 mm, an initial setting time of less than 10 minutes, and a final setting time of less than 4 hours.
[0049] In some embodiments, the rapid cementing material includes the following components in parts by mass: 140-160 parts of fly ash, 80-120 parts of slag powder, 8-15 parts of cement, 0.8-1.2 parts of cement early strength activator, 2-4 parts of accelerator and 50-70 parts of water.
[0050] In some embodiments, the rapid cementing material includes the following components in parts by mass: 150 parts of fly ash, 100 parts of slag powder, 10 parts of cement, 1 part of cement early strength activator, 3 parts of accelerating agent and 66 parts of water.
[0051] In some embodiments, the high-porosity filling material having a porosity of not less than 20% and a uniaxial compressive strength of not less than 0.2 MPa corresponds to a coal gangue particle size distribution of 0 to 20 mm.
[0052] In some embodiments, the high-porosity filling material having a porosity of not less than 30% and a uniaxial compressive strength of not less than 0.19 MPa corresponds to a coal gangue particle size distribution of 0 to 10 mm.
[0053] In some embodiments, the high-porosity filling material having a porosity of not less than 40% and a uniaxial compressive strength of not less than 0.14 MPa corresponds to a coal gangue particle size distribution of 0 to 5 mm.
[0054] In some embodiments, the mold 4 is transparent, so as to facilitate observation of the coal gangue accumulation state.
[0055] In some embodiments, the mold 4 is a hollow cylinder with an inner diameter of 50 mm and a height of 100 mm; a plurality of slurry discharge holes 7 are provided at the bottom of the mold 4 .
[0056] In some embodiments, the diameter of the grouting hole 5 and the grouting hole 7 is 5 mm.
[0057] In some embodiments, Figure 4 As shown, the number of the slurry discharge holes 7 is 9, and the slurry discharge holes 7 are evenly distributed at the bottom of the mold 4.
[0058] On the other hand, a high-porosity filling material with fast and efficient cementation of gangue prepared by the above-mentioned preparation method is provided. Figure 1 As shown, the gangue serves as a skeleton structure in the filling material, and the fast-bonding bonding material 2 is attached to the surface of the gangue 1 in a flocculent state, and the key contact points between the particles of the gangue 1 are bonded by the fast-bonding bonding material 2. The gangue 1 and the fast-bonding bonding material 2 are connected layer by layer, wherein a large number of pore structures 3 are formed between the particles of the gangue 1 to form a high-porosity filling material with a porosity of not less than 20% and a uniaxial compressive strength of not less than 0.14 MPa.
[0059] Example 1
[0060] A method for preparing a high-porosity filling material with rapid and efficient cementation of gangue is provided. The method comprises the following steps:
[0061] Step 1: In a transparent mold 4 (such as Figures 2 to 4 A layer of coal gangue with a particle size distribution of 0 to 5 mm is laid on the bottom of the coal gangue layer (as shown), and a quick-adhesive cementing material (comprising the following components by mass: 150 parts of fly ash, 100 parts of slag powder, 10 parts of cement, 1 part of cement early strength activator, 3 parts of quick-setting agent and 66 parts of water) is sprayed into the laid coal gangue layer through a pressurized nozzle, so that the quick-adhesive cementing material is evenly distributed on the surface of the coal gangue layer;
[0062] Step 2: Continue to lay a layer of coal gangue on the coal gangue layer after spraying the rapid adhesive bonding material, and repeat the above steps to lay coal gangue layer by layer and spray the rapid adhesive bonding material layer by layer until the coal gangue layer reaches the top of the mold, and then cover the upper cover of the mold;
[0063] Step 3: statically inject the quick-adhesive cementing material into the mold 4 through the injection hole 5 on the upper cover until the quick-adhesive cementing material appears at the bottom of the mold 4 and then stop injecting;
[0064] Step 4: After standing for 0.5 hours, a high-porosity filling material with rapid and efficient cementation of gangue is obtained.
[0065] Example 2
[0066] A method for preparing a high-porosity filling material with rapid and efficient gangue cementation is provided. Referring to Example 1, the only difference is that in step 1, the particle size distribution of the gangue is 0-10 mm.
[0067] Example 3
[0068] A method for preparing a high-porosity filling material with rapid and efficient gangue cementation is provided. Referring to Example 1, the only difference is that in step 1, the particle size distribution of the gangue is 0-20 mm.
[0069] Comparative Example 1
[0070] Provided is a method for preparing a dense filling body with fast and efficient cementation of gangue. The raw materials used in the dense filling body: the composition of coal gangue and fast cementation material is the same as that of Example 1, except that: the preparation method is to directly mix the coal gangue and the fast cementation material evenly, pour them into a mold, and prepare the dense filling body after standing for 0.5 hours.
[0071] Comparative Example 2
[0072] A method for preparing a dense filling body with rapid and efficient cementation of coal gangue is provided. Referring to comparative example 1, the only difference is that the particle size gradation of the coal gangue is 0-10 mm.
[0073] Comparative Example 3
[0074] A method for preparing a dense filling body with rapid and efficient cementation of coal gangue is provided. Referring to comparative example 1, the only difference is that the particle size gradation of the coal gangue is 0-20 mm.
[0075] Test Case
[0076] According to the "Standard for Test Methods for Performance of Ordinary Concrete Mixtures" (GB / T50080-2016), the slump, initial setting time, and final setting time of the fast-adhesive cementing materials of Examples 1 to 3 were tested, and the uniaxial compressive strength of the filling materials of Examples 1 to 3 and Comparative Examples 1 to 3 were tested according to the specific geological conditions of a mine.
[0077] The porosity Φ of the high-porosity filling material with rapid and efficient cementation of gangue in Examples 1 to 3 is calculated according to the following formula:
[0078]
[0079] Among them: m1 is the total mass of the mold and the coal gangue in it; ρ1 is the density of coal gangue; V0 is the internal volume of the mold; m2 is the total mass of the high-porosity filling material that is quickly and efficiently bonded to the mold and gangue after spraying and pouring; ρ2 is the density of the fast-bonding bonding material.
[0080] The results are as follows:
[0081] Table 1 Performance parameters of high-porosity filling materials prepared with different coal gangue particle sizes
[0082]
[0083] It can be seen from Table 1 that with the increase of the particle size of the coal gangue, the porosity of the gangue fast and efficient cemented high-porosity filling material obtained by the preparation method of the present invention gradually increases, and the uniaxial compressive strength gradually decreases.
[0084] Table 2 Performance parameters of dense filling body
[0085]
[0086] By comparing Table 1 and Table 2, it can be seen that the corresponding relationship between the porosity and the uniaxial compressive strength of the high-porosity filling materials of Examples 1 to 3 is: when the porosity is about 20%, the uniaxial compressive strength is 91.6% of the dense filling body; when the porosity is about 30%, the uniaxial compressive strength is 76% of the dense filling body; when the porosity is about 40%, the uniaxial compressive strength is 46.7% of the dense filling body.
Claims
1. A method for preparing a high-porosity filling material with rapid and efficient cementation of gangue, characterized in that: The following steps are involved: (1) According to the target porosity of the high-porosity filling material, a layer of coal gangue with a certain particle size distribution is laid on the bottom of the mold, and a fast-bonding cementing material is sprayed into the laid coal gangue layer through a pressurized nozzle. The fast-bonding cementing material includes the following components in parts by mass: 140 to 160 parts of fly ash, 80 to 120 parts of slag powder, 8 to 15 parts of cement, 0.8 to 1.2 parts of cement early strength activator, 2 to 4 parts of accelerated setting agent and 50 to 70 parts of water, so that the fast-bonding cementing material is evenly distributed on the surface of the coal gangue layer; (2) laying a layer of coal gangue on the coal gangue layer after spraying the rapid adhesive bonding material, and repeating the above steps to lay coal gangue layer by layer and spray the rapid adhesive bonding material layer by layer until the coal gangue layer reaches the top of the mold, and then covering the upper cover of the mold; (3) statically pouring a quick-adhesive cementing material into the mold through the grouting hole on the upper cover until the quick-adhesive cementing material appears at the bottom of the mold and then the pouring is stopped; (4) After standing for 0.5 h, a high-porosity filling material is obtained; (5) testing the porosity and uniaxial compressive strength of the high-porosity filling material; (6) by changing the particle size distribution of the coal gangue in step (1) to change the target porosity of the high-porosity filling material, repeating steps (2) to (5), and establishing a prediction model between the porosity and uniaxial compressive strength of the high-porosity filling material; (7) According to step (6), the particle size distribution of coal gangue corresponding to the high-porosity filling material having a porosity of not less than 20% and a uniaxial compressive strength of not less than 0.14 MPa is screened out; The fast-adhesive cementing material has a slump of 150 to 200 mm, an initial setting time of less than 10 minutes, and a final setting time of less than 4 hours.
2. The preparation method according to claim 1, characterized in that: The rapid cementing material comprises the following components in parts by mass: 150 parts of fly ash, 100 parts of slag powder, 10 parts of cement, 1 part of cement early strength activator, 3 parts of accelerating agent and 66 parts of water.
3. The preparation method according to claim 2, characterized in that: The particle size gradation of the coal gangue corresponding to the high-porosity filling material with a porosity of not less than 20% and a uniaxial compressive strength of not less than 0.2 MPa is 0 to 20 mm.
4. The preparation method according to claim 2, characterized in that: The particle size gradation of the coal gangue corresponding to the high-porosity filling material with a porosity of not less than 30% and a uniaxial compressive strength of not less than 0.19 MPa is 0 to 10 mm.
5. The preparation method according to claim 2, characterized in that: The particle size distribution of the coal gangue corresponding to the high-porosity filling material with a porosity of not less than 40% and a uniaxial compressive strength of not less than 0.14 MPa is 0 to 5 mm.
6. The preparation method according to claim 1, characterized in that: The mold is transparent.
7. The preparation method according to claim 1, characterized in that: The mold is a hollow cylinder with an inner diameter of 50 mm and a height of 100 mm; a plurality of slurry discharge holes are provided at the bottom of the mold.
8. The preparation method according to claim 7, characterized in that: The diameter of the grouting hole and the grouting hole is 5mm.
9. The high-porosity filling material with rapid and efficient cementation of gangue obtained by the preparation method according to any one of claims 1 to 8, characterized in that: The quick-bonding material is attached to the surface of the coal gangue in the form of flocs, and is bonded between the key contact points between the particles of the coal gangue through the quick-bonding material. The coal gangue and the quick-bonding material are connected layer by layer to form a high-porosity filling material with a porosity of not less than 20% and a uniaxial compressive strength of not less than 0.14MPa.
Citation Information
Patent Citations
Red mud solidifying and gelatinizing compound, preparation method thereof and in-situ red mud solidifying method
CN108793794A
Coal gangue-based composite geopolymer grouting filling material and preparation method thereof
CN111018423A
Gangue filling cementing entry retaining system and method
CN111485912A
Inorganic grouting material based on coal gangue as well as preparation method and application of inorganic grouting material
CN115490446A
Method for ecological filling with mixed coal gangue and fly ash
US20230097415A1
